Phosphate sources derived from wastewater and sewage sludge: agronomic potential - Raniro, Henrique Rasera (2021)
Phosphorus (P) is a nutrient essential for energy metabolism and DNA/RNA production in plants. In Brazil, high amounts of P fertilizers are applied onto agricultural fields every year to supply plants demand, creating an economic, environmental and supply chain risk scenario. To overcome those issues, phosphate sources recycled from wastewaters and sewage sludge merge as an alternative to conventional fertilizers, due to their agronomic potential use and renewable origins, reducing environmental impact while contributing to sustainable agriculture and circular economy. Struvite and hazenite are minerals recovered via chemical precipitation from wastewaters, while ashdec can be obtained through thermochemical treatment of sewage sludge ashes. Low water-solubility and late release, more aligned with plants demand, are common characteristics of these recycled fertilizers, what could improve the efficiency of P fertilization. Here, we evaluated the solubilization of struvite, hazenite ashdec and triple superphosphate (TSP), their P release dynamics and their impact on the solution pH and on soil P fractions through an incubation leaching columns experiment. We also assessed their agronomic potential and efficiency compared to TSP (chosen conventional source) through a greenhouse trial for two 90 days cycles of sugarcane (Saccharum spp.) under those phosphate sources and three P doses (30, 60 and 90 mg kg-1). Dry mass yield (DMY), biometric parameters, nutrient uptake and soil P fractions were analyzed for each harvest. Our findings showed that while the recycled sources are less water-soluble and promote late P release, solubilizing less P than TSP in the initial period, plants were able to improve P utilization from these sources, since struvite (both harvests) and hazenite (first cycle) outperformed, while ashdec was comparable to TSP in DMY and P uptake. In the first 90 d, all three recycled sources showed higher soil labile P levels than TSP, which was the only source increasing the non-labile pool by the end.